Assessment of non-timber forest products (NTFPs) in Behali Reserve Forest, Assam, Northeast India - Borah, Dipankar; Tangjang, Sumpam; Das, Abhaya Prasad; Upadhaya, Ankur; Mipun, Puranjoy (Ethnobotany Research and Applications, 2020)
Background: Non-timber forest products are defined as all biological materials other than timber, which are extracted from forests for human use. Uses of various NTFPs have shown significant progress in cultural subsistence, commercial purposes, bioprospecting and sustainable support to forest biodiversity. The present research was conducted in the area to document NTFPs of plants origin with their relative importance, to record information for future investigation and discovery of novelty in drug use, and to edify the local communities on sustainable forest management. Methods :The study was aimed to assess the Non-timber forest products of Behali Reserve Forest of Assam. Data was collected from 67 households belonging to two communities (Karbi and Munda), covering almost 50% of the total households of the studied area using semi-structured questionnaires, personal interviews, group discussions and transect walks from 2017 to 2019. Results: A total of 100 plants falling under 87 genera and 56 families were reported. Urticaceae with 6 taxa was the most dominant family. Trees with 35% were the most dominant group, followed by shrubs (28%), climbers (22%) and herbs (15%). Out of the reported NTFPs, 51 taxa (51%) were edibles, 23 taxa (23%) had ethnomedicinal importance, and 48 taxa (48%) are treated as having miscellaneous uses. Use value of all the reported taxa ranged from 0.01 to 0.13. Zanthoxylum oxyphyllum, Hodgsonia macrocarpa, Aristolochia cathcartii and Aristolochia assamica have high UV indicating that these taxa are most important for the studied population. Informant consensus factor was calculated for the different ailments recorded and a total of seven taxa were found to have above 70% fidelity level values, showing high reliance of the forest dependent people on these taxa. Conclusiosn: The study illustrates a high diversity of NTFPs in the area as well as an intricate relation with the people residing in the fringes of the forest. Anthropogenic activities such as construction of roads, cutting of forests for jhum (shifting) cultivation, natural calamities like landslides etc., were observed to be serious threats to native biodiversity. It is recommended to provide skill development trainings and financial support for the installation of renewable and alternative energy technologies to minimize the use of forest resources in Behali Reserve Forest for better forest sustainability. Key words: Assam, Assesment, Behali Reserve Forest, Non-timber forest products, quantitative approach, bio-resources